2019
DOI: 10.21449/ijate.482005
|View full text |Cite
|
Sign up to set email alerts
|

Improved Performance of Model Fit Indices with Small Sample Sizes in Cognitive Diagnostic Models

Abstract: Selecting an appropriate cognitive diagnostic model (CDM) for data analysis is always challenging. Studies have explored several model fit indices for CDMs. The common results of these studies indicate that Qmatrix misspecifications lead to poor performance of the model fit indices in the context of CDMs. Thus, this study explored whether model fit indices improve performance with a modified Q-matrix. The average class size has reduced to 23 students in Taiwan because of the low birth rate; therefore, the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Results indicated that performance of fit indices appeared to increase as the sample size increased. Tzou and Yang (2019) also compared the performance of model fit indices in CDMs using small sample sizes (i.e., 50, 75, 100, and 200) and showed that AIC (Akaike, 1974) performed better than other indices. Similarly, Hu et al (2016) evaluated model fit for CDMs using sample sizes of 200, 500, and 1,000 and showed that performances of the three relative fit statistics AIC, BIC (Schwarz, 1978), and CAIC (Bozdogan, 1987) improved when sample size increased.…”
Section: Introductionmentioning
confidence: 99%
“…Results indicated that performance of fit indices appeared to increase as the sample size increased. Tzou and Yang (2019) also compared the performance of model fit indices in CDMs using small sample sizes (i.e., 50, 75, 100, and 200) and showed that AIC (Akaike, 1974) performed better than other indices. Similarly, Hu et al (2016) evaluated model fit for CDMs using sample sizes of 200, 500, and 1,000 and showed that performances of the three relative fit statistics AIC, BIC (Schwarz, 1978), and CAIC (Bozdogan, 1987) improved when sample size increased.…”
Section: Introductionmentioning
confidence: 99%
“…The study's findings revealed that when item discrimination, sample size, and number of items increased, the estimation accuracy for attributes improved, and when the number of attributes and the degree of the misspecification for a Q-matrix were large, the estimation accuracy deteriorated. Yang et al (2019) investigated how fit indices performed in small sample sizes (i.e. 50, 75, 100, and 200) and confirmed that Akaike information criterion (AIC) is an appropriate choice for model selection under small sample conditions.…”
Section: Introductionmentioning
confidence: 86%